Dynamic processes in the main oil pipelines. Part I. The analysis of causes of leakage occurrence in oil pipelines and leak identification methods - Bajoraitytė, Ingrida; Bogdevičius, Marijonas (Transport, 2002)
The causes of accidental damages and the damages in oil pipelines are presented. The analysis of identification methods of leaks occurring due to the damages of the linear part of the main oil pipelines is carried out. The momentum and continuity equations of viscous compressible fluid in a pressure pipeline are presented. Differential equations of fluid movement in the oil pipeline are solved by the method of characteristics. Vatiation diagrams of pressure and velocity of fluid of a leaking oil pipeline are presented.First Published Online: 19 Dec 2011